Epicurs Happiness Theory - Al-Daher, Suleiman; Ammar, Hanaa (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The theory of happiness occupies an important place in the history of philosophical thought. It has attracted attention in the history of human and moral thought and the philosophers went on to interpret it in different and different direction. The philosophical sciences are classified in three types: logic, nature, morality, and the theory of happiness comes within philosophy at the Epicririan. Epicor addressed the issue of happiness as a delicate and profound treatment stemming from the Greek nature of life, social and economic crises and political collapse as a result of the wars with the Macedonians, seeking the nature of happiness and all that brings pleasure and pleasure to man, relieves burdens of misery and fears, showing him the path of happiness. تشغل نظرية السعادة مكانة مهمة في تاريخ الفكر الفلسفي، وقد لاقت اهتماماً كبيراً عبر تاريخ الفكر الإنساني والأخلاقي، وذهب الفلاسفة في تفسيرها اتجاهات مختلفة ومتباينة. صنفت الأبيقورية العلوم الفلسفية على ثلاثة أنواع: المنطق، الطبيعة، الأخلاق، وتأتي نظرية السعادة في إطار الفلسفة الأخلاقية عند الأبيقوريين. وقد عالج أبيقور مسألة السعادة معاجلةً دقيقة وعميقة، نابعة من طبيعة الحياة اليونانية المترددة بين الأزمات الاجتماعية والاقتصادية والانهيارات السياسية نتيجة الحروب مع المقدونيين، باحثاً عن طبيعة السعادة وكل ما يجلب اللذة والسرور للإنسان، مخففاً عنه أعباء الشقاء والمخاوف، مبيناً له طريق السعادة.